1972
DOI: 10.1139/p72-382
|View full text |Cite
|
Sign up to set email alerts
|

The Resonant Faraday Effect

Abstract: The resonant Faraday effect occurs for radiation at frequencies close to the absorption lines of a magnetoactive material. In the paper we present a theory for isolated absorption lines with Voigt profiles. The background source is also assumed to have a Voigt profile. The theory shows how the resonant Faraday effect can be used to determine relative transition probabilities, as well as the magnitude of the Lorentzian component of the line profiles.Experimental results for an argon plasma are presented and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…With these refinements, Camm and Curzon (1972) obtained excellent agreement between the computed and experimental irradiance as a function of B and achieved as low as 1% uncertainty for relative transition probabilities. In addition these authors were able to determine the value of a to 10%.…”
Section: Magneto-rotation Techniques If An Absorption Cell Containing...mentioning
confidence: 82%
See 2 more Smart Citations
“…With these refinements, Camm and Curzon (1972) obtained excellent agreement between the computed and experimental irradiance as a function of B and achieved as low as 1% uncertainty for relative transition probabilities. In addition these authors were able to determine the value of a to 10%.…”
Section: Magneto-rotation Techniques If An Absorption Cell Containing...mentioning
confidence: 82%
“…They used a neon Geissler tube for the source and found that the experimental and theoretical irradiance distributions did not always agree to within the experimental uncertainties. Subsequently Camm and Curzon (1972) in an elegant and productive investigation of Ar I used identical discharge tubes for both the source and the absorbing atoms (S and the test cell shown in figure 4). In addition, they removed the effects of radial density gradients in the test cell by restricting the aperture of the source beam to the centre of the cell.…”
Section: Magneto-rotation Techniques If An Absorption Cell Containing...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1960-1970s, motivated by the determination of the oscillator strength of resonance lines of rare-gas atoms, but also for testing the applicability of different collision broadening theories, several groups have measured the pressure broadening coefficients of different argon lines. The resonance Faraday effect on some argon lines absorbed by metastable atoms has been used in 24,25 , but most of the line profiles were obtained from the analysis of the profile of plasma induced emission, by scanning Fabry-Perot interferometer 26,27,28 or with a spectrometer 29,30,31,32 . However, the necessary correction for the apparatus function of the experimentally recorded spectral profiles of the lines introduced large uncertainty on deduced broadening coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…A filter based on the anomalous dispersion of the Faraday rotation in the resonance lines of certain atomic gases was first described and demonstrated by Ohman (1956). The theoretical framework for the resonant Faraday effects has been established (Camm et al 1972, Roberts et al 1980, Yeh 1982, Chen et al 1987. Yin and Shay (1991) developed the theoretical framework for FADOF based on ground-state transitions by using a quantum-mechanical treatment of the resonant Faraday effect.…”
Section: Introductionmentioning
confidence: 99%